Analysis of cesarean section rates based on robson's classification and its outcomes at a governmental tertiary referral teaching hospital in the Sistan and Baluchestan Province, Iran - Zahra Moudi (Kashan University of Medical Sciences, 2022)
Background: Timely cesarean section (CS) can be lifesaving, but its overuse may lead to health risks. Robson classification is a standard tool for monitoring and comparing CS rates at all levels. Objectives: The objective of this study is to analyze the CS rates based on Robson classification and its outcomes in a governmental tertiary referral teaching hospital in Zahedan city, Iran. Methods: A cross-sectional study was carried out on all CS (n = 1763) performed in Ali-Ibn-Abitaleb Hospital of Zahedan city from September 22 to March 19, 2019. Data were extracted from women's paper-based files. Descriptive analyses were performed. The Chi-square test was used to test the differences between groups. The odds ratio was used to calculate the risk of adverse maternal and perinatal outcomes in women with and without a previous CS. Results: The overall rate of CS was 44.81%. Women with previous CS (Robson group 5) were the largest contributors to the overall CS rate (39.82%), followed by Robson group 10 (i.e., women with a single cephalic pregnancy at ≤36 weeks' gestation: 19.45%). The CS rate in women in Robson groups 1 and 2 was 9.93% and 5.61%, respectively. The main indications for CS among nulliparous women were fetal distress (42.99%), malpresentation (14.95%), and prolonged and obstructed labor (10.98%). Adverse maternal outcomes were similar in women with and without a previous CS. Conclusions: The Robson classification system showed a high rate of CS in the study setting, and many CSs were performed in women with low-risk pregnancies.